2020
DOI: 10.3390/math8071148
|View full text |Cite
|
Sign up to set email alerts
|

On Numerical Analysis of Carreau–Yasuda Nanofluid Flow over a Non-Linearly Stretching Sheet under Viscous Dissipation and Chemical Reaction Effects

Abstract: This work reports the Carreau–Yasuda nanofluid flow over a non-linearly stretching sheet viscous dissipation and chemical reaction effects. The coupled system of non-linear partial differential equations are changed into a system of linear differential equations employing similarity equations. The spectral quasi-linearization method was used to solve the linear differential equations numerically. Error norms were used to authenticate the accuracy and convergence of the numerical method. The effects of some the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…to produce initial conditions for subsequent subintervals (ε p = 2, 3, 4, …, ) in τ, the multidomain is utilized on the local linearization method (LLM) schemes ( 16)- (19). Accordingly, we must solve…”
Section: Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…to produce initial conditions for subsequent subintervals (ε p = 2, 3, 4, …, ) in τ, the multidomain is utilized on the local linearization method (LLM) schemes ( 16)- (19). Accordingly, we must solve…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…It was reported that the incorporated Carreau-Yasuda model produced superior approximations at critical locations. Shateyi and Muzara 19 employed the spectral quasilinearization method to analyze the flow of Carreau-Yasuda nanofluid past a stretching sheet with viscous dissipation along with chemical reaction and found that the spectral quasilinearization method provides extremely efficient and reliable solutions for nonlinear differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…Malik et al (Khan et al, 2020a(Khan et al, , 2020b provide information on the MHD-based Darcy-Forchheimer's CY nanofluid flow. The numerical data of CY nanofluid flow across a nonlinearly stretching surface with the effects of chemical reaction and viscous dissipation has been obtained by Shateyi and Muzara (2020). A numerical result for the CY nanofluid in a permeable medium containing bioconvective motile microorganisms was given by Waqas et al (2021), Fadaei et al (2022) examined the melting process of CY fluid in a shell and tube heat exchanger saturated with a porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Shafiq et al [20] investigated the heat and mass transport of a bio-convective hyperbolic tangent nanofluid containing motile microorganisms across an exponentially vertical stretch sheet. Several studies [21][22][23] have been completed and are available in the literature. Now it is a fact that an optimized enhancement of heat transfer in fluids can be achieved when nano-particles of more kinds are suspended in the fluid.…”
Section: Introductionmentioning
confidence: 99%